1989
DOI: 10.1111/j.1096-3642.1989.tb02314.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel ultrastructure and masticatory function in molars of the American opossum, Didelphis virginiana

Abstract: Maxillary and mandibular molars of the American opossum, Didelphis virginiana L., were viewed in the scanning electron microscope (SEM) after acid‐etching or after cutting and acid‐etching. Observations were made on enamel prism patterns as they relate to functional properties of the tooth at a particular site. Molars at different stages of wear were also observed under a dissecting microscope; worn surfaces were correlated with function and enamel ultrastructure. Pounding surfaces of molar cusps wear more rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
(21 reference statements)
3
29
0
1
Order By: Relevance
“…In contrast, Stern et al (1989) suggested that the much more extensive molar cusp wear in Didelphis is the result of abrasion by food particles driven parallel to the surface. It should be noted, however, that if adhesion between opposing surfaces accounts for formation of small microwear pits (Teaford and Runestad, 1992), then surface-parallel force also may be a factor in galago cuspal abrasion.…”
Section: Occlusal Enamel Structurementioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, Stern et al (1989) suggested that the much more extensive molar cusp wear in Didelphis is the result of abrasion by food particles driven parallel to the surface. It should be noted, however, that if adhesion between opposing surfaces accounts for formation of small microwear pits (Teaford and Runestad, 1992), then surface-parallel force also may be a factor in galago cuspal abrasion.…”
Section: Occlusal Enamel Structurementioning
confidence: 89%
“…Cusps of Didelphis molars are much more extensively worn than those of galago molars. Unlike the blunted cusps and ridges of worn galago molars, worn Didelphis molar cusps and ridges form sharp cutting edges, a result of the rapid wear of apices of cusps and crests in conjunction with wear resistance of wear crest and cusp slopes (Stern et al, 1989). The different wear patterns in these two animals are a general indication of differences in molar function.…”
Section: Occlusal Enamel Structurementioning
confidence: 97%
See 2 more Smart Citations
“… mammalian teeth have evolved such that individual prisms are optimally orientated to maximally resist abrasion, even if this means that prism distribution within a tooth is asymmetric (14, 15); the angle at which an individual prism meets the tooth surface will determine its resistance to wear (16, 17). …”
Section: Hsbs and Tooth Surface Lossmentioning
confidence: 99%